Identification of microRNA-21 target genes associated with hair follicle development in sheep - Zhai, Bo; Zhang, Lichun; Wang, Chunxin; Zhao, Zhuo; Zhang, Mingxin; Li, Xu (PeerJ, 2019)
Aim The target molecule regulatory function of microRNA-21 (miR-21) in multiple signalling pathways has become a main focus of genetic and pharmacological regulatory studies of various diseases. The identification of target genes for miRNA-21 in the development of hair follicles can provide new research pathways for the regulation of cell development. Methods In the present study, eight six-month-old ewes from Super Merino (SM) and Small Tailed Han (STH) sheep breeds were selected. Target prediction and dual-luciferase wild-type and mutant vectors were used to identify the target genes of miR-21. Quantitative reverse transcription polymerase chain reaction (RT-qPCR) and bioinformatics analysis were conducted to analyze the effects of miR-21. Results The results show that the expressions of CNKSR2, KLF3 and TNPO1 were downregulated by miRNA-21 at rates of 36%, 26% and 48%, respectively. Moreover, there was a significant negative correlation between the expression of miR-21 and the three target genes in sheep with two extreme phenotypes. The expression of microRNA-21in October was significantly lower than that in January and February; while the expression of CNKSR2, KLF3 and TNPO1 in October was higher than that in January and February. Conclusions: These results suggest that CNKSR2, KLF3 and TNPO1 are three newly discovered target genes of miR-21 and might be involved in the effects of miR-21 on hair follicle development.
Keywords: microRNA-21; Sheep; Hair follicles